2010
DOI: 10.1590/s1413-85572010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Resiliência em estudantes do ensino médio

Abstract: O objetivo do estudo foi avaliar a resiliência em estudantes do Ensino Médio e sua associação com variáveis sociodemográficas e contribuição da escola em seu desenvolvimento pessoal. A amostra foi composta de 140 alunos de uma Escola Estadual de uma cidade da região metropolitana de Porto Alegre. Foram utilizados, como instrumentos de pesquisa, um questionário para levantamento de variáveis demográficas e sociais e a Escala de Resiliência, adaptada por Pesce, Assis, Avanci, Santos, Malaquias e Carvalhaes (2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(8 reference statements)
1
3
1
8
Order By: Relevance
“…Younger students on the other hand, showed less resilience in all dimensions. These results corroborate those obtained by Peltz, Moraes and Carlotto (2010), where the age variable strongly, and statistically, interferes with the individual's resilience. Results from table 4 indicate that students living in rural areas revealed more resilience, with specific focus on "perseverance" and "total resilience values".…”
Section: Resultssupporting
confidence: 90%
“…Younger students on the other hand, showed less resilience in all dimensions. These results corroborate those obtained by Peltz, Moraes and Carlotto (2010), where the age variable strongly, and statistically, interferes with the individual's resilience. Results from table 4 indicate that students living in rural areas revealed more resilience, with specific focus on "perseverance" and "total resilience values".…”
Section: Resultssupporting
confidence: 90%
“…This result corroborates the studies of Dell'Aglio, Koller e Yunes (2006) and Donahue (2001), which showed the importance of resilience indicators in life planning, such as firm acceptance of reality, beliefs, supported by values, strongly supporting that life is meaningful, and the ability to improvise. Brandão et al (2011), Peltz et al (2010 and Ryff et al (2012) emphasize the importance of resilience in resolving difficult situations. Haslamet al (2009) highlighted that self-determination and self-guidance are the determinant aspects for subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Masten (2011) andPeltz, Moraes andCarlotto (2010) define resilience as the ability of a dynamic system to support or recover from significant challenges that threaten its stability, viability or development. To Ryff et al (2012), resilience is the ability of individuals to recover and main their well-being when facing adverse situations.…”
mentioning
confidence: 99%
“…Como visto em outros trabalhos (Peltz, Moraes & Carlotto, 2010;Pesce & cols., 2004), o estudante que demonstra as características da resiliência percebe-se como capaz de enfrentar as dificuldades encontradas, nos campos social e acadêmico, o que se reflete positivamente nos resultados escolares. (Assis & cols., 2006).…”
Section: Discussionunclassified